Cardiovascular-disease mortality trends and oral-contraceptive use in young women. - Beral, V (1976)
Analysis of mortality trends in 21 countries indicates that, since oral contraceptives first became available, changes in mortality from non-rheumatic heart-disease and hypertension (I.C.D. 400-429), cerebrovascular disease (I.C.D. 430-439), and all non-rheumatic cardiovascular diseases (I.C.D. 400-469) among women aged 15-44 years have been strongly associated with changes in the prevalence of oral-contraceptive use in each country. This relationship is highly specific for women of reproductive age. The relative risks of death from heart-disease and hypertension, cerebrovascular disease, and all cardiovascular diseases for women using oral contraceptives compared with non-users were estimated to be 5 to 1,2 to 1, and 3 to 1 respectively. These findings suggest that the range of vascular diseases affected by oral-contraceptive use and the size of the associated risks may be greater than previously recognised. Furthermore, the increased risks of cardiovascular disease might exist not only with the pills containing high oestrogen doses, but also with the new "lower dose" pills.